2009
DOI: 10.1186/cc7867
|View full text |Cite
|
Sign up to set email alerts
|

Long-term survival of chronic dialysis patients following survival from an episode of multiple-organ failure

Abstract: Introduction This study aimed to examine the long-term outcome for patients with end-stage renal failure (ESRF) who survived multiple-organ failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
37
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 15 publications
2
37
1
Order By: Relevance
“…Other studies have reported ICU mortality rates of 9% to 44% for chronic dialysis patients [4, 5, 7, 8, 1015, 1820]. …”
Section: Short-term Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have reported ICU mortality rates of 9% to 44% for chronic dialysis patients [4, 5, 7, 8, 1015, 1820]. …”
Section: Short-term Outcomesmentioning
confidence: 99%
“…This significant increase in mortality is however not surprising, given the higher illness severity scores of ESRD patients on admission to ICU in this study. In 199 dialysis-dependent patients requiring support of two or more organ systems (including RRT), ICU mortality was 44% [18], a figure similar to ICU mortality for patients with multiorgan failure which can range from 20% to 95% depending on the number of organs involved and underlying comorbidity. …”
Section: Short-term Outcomesmentioning
confidence: 99%
“…While studies that have evaluated the impact of ICU admission on the long-term survival of dialysis patients beyond 6 months report conflicting results [8,9,20,21], overall, ESRD patients who survive past hospital discharge appear to have outcomes comparable to those of the general dialysis population.…”
Section: Epidemiology Of Critical Illness In Dialysis Patientsmentioning
confidence: 99%
“…Chapman et al [20] reported that 62 (56%) of the dialysis patients who survived past ICU discharge were alive at 2 years. When the deaths that occurred 1 month after ICU discharge were eliminated, the difference between the group of dialysis patients with an episode of critical illness and registry controls was no longer significant; the majority of these early deaths occurred in hospital.…”
Section: Epidemiology Of Critical Illness In Dialysis Patientsmentioning
confidence: 99%
“…This situation has cumulated in a rise in critical illness and the need for admission to the intensive care unit (ICU) (5)(6)(7). Despite this escalation in ICU admission, little literature is available about the causes of critical illness, prognosis, or long-term outcomes to guide health care providers (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18).…”
mentioning
confidence: 99%